Changes of local microenvironment and systemic immunity after acupuncture stimulation during inflammation: A literature review of animal studies - Yu, Wei-Lien; Park, Ji-Yeun; Park, Hi-Joon; Kim, Seung-Nam (Frontiers in Neurology, 2023)
An increasing number of studies have demonstrated the underlying mechanisms by which acupuncture therapy mediates both local and systemic immunomodulation. However, the connection between alterations in the local microenvironment and the resulting change in systemic immunity remains unclear. In this review, we focus on cell-specific changes in local immune responses following acupuncture stimulation and their link to systemic immune modulation. We have gathered the most recent evidence for chemo- and mechano-reactive changes in endothelial cells, neutrophils, macrophages, and mast cells in response to acupuncture. Local signaling is then related to the activation of systemic neuro-immunity including the cholinergic, adrenal, and splenic nervous systems and pain-related neuromodulation. This review aims to serve as a reference for further research in this field.